Thromboelastography profiles for controlled circulatory death donors: Validating the role of heparin. Issue 2 (29th November 2021) - Crannell, W. Christian; Sally, Mitch; McConnell, Keeley; Connelly, Chris; Maynard, Erin; Dewey, Elizabeth; Abt, Peter; Enestvedt, C. Kristian
Abstract: Controlled donation after circulatory death (cDCD) liver transplants are associated with increased ischemic‐type biliary complications. Microvascular thrombosis secondary to decreased donor fibrinolysis may contribute to bile duct injury. We hypothesized that cDCD donors are hypercoagulable with impaired fibrinolysis and aim to use thromboelastography to characterize cDCD coagulation profiles.